Application of high voltage dividers for power quality indices measurement - Anokhin, Y.L.; Brzhezytskyi, V.O.; Haran, Ya.O.; Masliuchenko, I.M.; Protsenko, O.P.; Trotsenko, Ye.O. (Електротехніка і електромеханіка, 2017)
Introduction. Determination of power quality indices in high-voltage power grids allows to find the reasons for the deterioration
of the power quality. The relevant national and International Standards for power quality contain relevant norms of quality
indices and requirements for their accuracy measurement. Problem. The most complicated part in the process of measuring the
power quality indices at high voltage is the selection of the corresponding high-voltage scale voltage converters. Therefore,
comparing the requirements of IEC 61000-4-30 to high voltage scale voltage converters is an important task. Goal. Analysis of
the International Standard IEC 61000-4-30 requirements feasibility for measuring the indices of power quality in high-voltage
electrical networks using different types of high-voltage scale voltage converters. Methodology. Comparison of the requirements
of IEC 61000-4-30 Standard to high-voltage scale voltage converters, when measuring power quality indices, with the
characteristics of high voltage electromagnetic transformers used in Ukraine, and with promising developments of high-voltage
converters of other types. Results. It is shown in the study that in order to fulfill some of the requirements for class A of IEC
61000-4-30, the characteristics of electromagnetic voltage transformers should be determined in the substation conditions using
mobile calibration high-voltage laboratories. To meet all the requirements for Class A IEC 61000-4-30, it is recommended to use
broadband high-voltage dividers of resistive-capacitive type. Originality. In study it is shown firstly that all the requirements of the
IEC 61000-4-30 Standard for high-voltage scale voltage converters can be performed on the basis of the use of broadband
resistive-capacitive damped voltage dividers. Practical value. Expositions of specific types of resistive-capacitive high-voltage
dividers are presented, their parameters are confirmed by the results of state metrological certification. Цель. Анализ выполнимости требований международного стандарта IEC 61000-4-30 при измерениях показателей
качества электроэнергии в высоковольтных электрических сетях с использованием различных типов
высоковольтных масштабных преобразователей напряжения. Методика. Сравнение требований стандарта IEC
61000-4-30 к высоковольтным масштабным преобразователям напряжения, при измерении показателей качества
электроэнергии, с характеристиками электромагнитных трансформаторов высокого напряжения, применяемых в
Украине, и с перспективными разработками масштабных преобразователей высокого напряжения других типов.
Результаты. Показано, что для выполнения части требований по классу А IEC 61000-4-30 характеристики
электромагнитных трансформаторов напряжения должны быть определены в условиях подстанции с помощью
мобильных поверочных высоковольтных лабораторий. Для выполнения всех требований по классу А IEC 61000-4-30
рекомендуется использование высоковольтных широкополосных делителей напряжения емкостно-омического типа.
Научная новизна. Впервые показано, что все требования стандарта IEC 61000-4-30 к высоковольтным масштабным
преобразователям напряжения могут быть выполнены на основе использования широкополосных емкостноомических демпфированных делителей напряжения. Практическая значимость. Представлены экспозиции
конкретных типов емкостно-омических делителей высокого напряжения, их параметры, подтвержденные
результатами государственной метрологической аттестации.